2019
DOI: 10.1002/admt.201800674
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Soft Actuators Based on Anisotropic Paper/Polymer Bilayer Toward Bioinspired Applications

Abstract: Designing artificial muscle actuators with diversely complex deformation and multifunction is crucial to the soft robots and their bioinspired applications. Herein, by combing the hygroexpansion and thermal expansion commonly existed in nature, electrically driven paper‐based bilayer actuator is fabricated by a simple printing method. This actuator exhibits large (270°) and anisotropic deformation coupled with features of low‐cost, superior stability, and additional reversible color‐change function. More impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 47 publications
0
44
0
Order By: Relevance
“…Elastomers [37][38][39], resin [40,41], SMP (MPCL) [42], other polymer [43], paper [43,44], micro-and nanofillers [45] Swelling Hydrogels [46][47][48][49][50], paper [43], LCN [51], SMP [48,[52][53][54][55], cross-linked PCL [56], other polymers [43,[57][58][59][60][61][62][63][64]…”
Section: Thermal Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elastomers [37][38][39], resin [40,41], SMP (MPCL) [42], other polymer [43], paper [43,44], micro-and nanofillers [45] Swelling Hydrogels [46][47][48][49][50], paper [43], LCN [51], SMP [48,[52][53][54][55], cross-linked PCL [56], other polymers [43,[57][58][59][60][61][62][63][64]…”
Section: Thermal Expansionmentioning
confidence: 99%
“…Among them, elastomers [37][38][39], resins [40,41] or other polymers [43] have been reported. Paper is commonly used to add asymmetry to the design [43,44] (Section 2.4). Alternatively, SMP materials, detailed in Section 2.3.1, can be used as thermally expansive materials [42].…”
Section: Soft Isotropic Transducersmentioning
confidence: 99%
“…Reproduced with the permission of 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. (F) Electrically driven paper-based bilayer actuator (Hu et al, 2019). Reproduced with the permission of 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.…”
Section: Shape-changing Structuresmentioning
confidence: 99%
“…As shown in Figure 8E, the 3D-printed starfish soft robot can realize swimming and wrapping motions under the guidance of magnetic fields. Inspired by the moisture induced deformation of the pine cone, the electrically driven paper-based bilayer actuator is fabricated by a simple and scalable screen-printing method (Hu et al, 2019), as shown in Figure 8F. In the paper-based actuator, the polymer and silver nanoparticles are the deformation active units and energy conversion components, respectively.…”
Section: Shape-changing Structuresmentioning
confidence: 99%
“…Besides biomimetic hydrostats that rely on exertion of hydraulic pressure on relatively inextensible boundaries, liquid movement can induce motion via other biomimetic mechanisms such as swelling. Actuators based on swelling of hygroscopic materials exposed to humidity gradients (Shin et al, 2018;Hu et al, 2019) provide straightforward and biomimetic design and utilize abundant biomaterials as well as humidity as the energy source, yet suffer in control challenges. A practical, micro-scale liquid-pumping solution is needed.…”
Section: Introductionmentioning
confidence: 99%